The Implementation of CTL Approach in Teaching Speaking at College Students Akademi Kebidanan Keluarga Bunda Jambi - Rahmah Rahmah (International Journal of Language Teaching and Education, 2018)
The study aimed at describing the use of contextual teaching and learning on students’ speaking skills. Apart from analyzing the students’ problems, it also looked at improvement in the students’ speaking skills through the use of contextual teaching and learning. The research involved of the third semester students at KeluargaBunda Jambi Midwifery Academy academic year 2015/2016. The students were 50 students consists of 25 as experimental group and 25 students as control group. This was an experimental research, conducted in experimental group and control group. Each group consists of five meeting. The material for the first meeting was about examination of pregnancy. The second meeting was about examination of Leopold. The third meeting was about baby’s care. The fourth meeting was about breast self-exam. And the last meeting was about infuse. In collecting the data, the researcher used observation and recording. The findings show that there was a significant effect between students who taught using CTL and who taught by using conventional teaching. The test result of experimental group after being analyzed was 0.023 < 0.05. The analysis was conducted the mean score of each category both pretest and posttestin experimental group was higher than control group. Therefore, it can be concluded that contextual teaching and learning can help teacher to teach the students easier and students are easier to understand the material.